Invasive mammals and habitat modification interact to generate unforeseen outcomes for indigenous fauna. Issue 7 (1st October 2013) - Norbury, Grant; Byrom, Andrea; Pech, Roger; Smith, James; Clarke, Dean; Anderson, Dean; Forrester, Guy
Abstract : Biotic invasions and habitat modification are two drivers of global change predicted to have detrimental impacts on the persistence of indigenous biota worldwide. Few studies have investigated how they operate synergistically to alter trophic interactions among indigenous and nonindigenous species in invaded ecosystems. We experimentally manipulated a suite of interacting invasive mammals, including top predators (cat Felis catus, ferret Mustela furo, stoat M. erminea ), herbivores (rabbit Oryctolagus cuniculus, hare Lepus europaeus ), and an insectivore (hedgehog Erinaceus europaeus occidentalis ), and measured their effects on indigenous lizards and invertebrates and on an invasive mesopredator (house mouse Mus musculus ). The work was carried out in a grassland/shrubland ecosystem that had been subjected to two types of habitat modification (widespread introduction of high‐seed‐producing pasture species, and areas of land use intensification by fertilization and livestock grazing). We also quantified food productivity for indigenous and invasive fauna by measuring pasture biomass, as well as seed and fruit production by grasses and shrubs. Indigenous fauna did not always increase following top‐predator suppression: lizards increased on one of two sites; invertebrates did not increase on either site. Mesopredator release of mice was evident at the site where lizards did not increase, suggesting negative effects of mice on lizard populations. High mouse abundance occurred only on the predator‐suppression site with regular production of pasture seed, indicating that this food resource was the main driver of mouse populations. Removal of herbivores increased pasture and seed production, which further enhanced ecological release of mice, particularly where pasture swards were overtopped by shrubs. An effect of landscape supplementation was also evident where nearby fertilized pastures boosted rabbit numbers and the associated top predators. Other studies have shown that both suppression of invasive predators and retiring land from grazing can benefit indigenous species, but our results suggest that the ensuing vegetation changes and complex interactions among invasive species can block recovery of indigenous fauna vulnerable to mesopredators. Top‐down and bottom‐up ecological release of mesopredators and landscape supplementation of top predators are key processes to consider when managing invaded communities in complex landscapes.